Study of M99o and long-lived impurities produced in the Mnato(γ, x) reactions using an electron beam. (December 2020) - Ahmed, Arshiya Anees; Wrońska, Aleksandra; Magiera, Andrzej; Curcio, Alessandro; Jaglarz, Magdalena; Wawrzyniak, Adriana
Abstract: We discuss the possibility of producing M 99 o radioisotope using an electron beam accelerated in the linac injector of the SOLARIS synchrotron. M 99 o with a half-life of 65.94 h, is a parent of the medically important radioisotope T 99 m c ( T 1 / 2 = 6  h ) . In our study M 99 o was produced from M nat o ( γ, x ) reaction using Bremsstrahlung γ radiation generated by 60, 100 and 200 MeV electron beams hitting a tungsten radiator located in front of the target. The activity of M 99 o was analysed by off-line γ spectroscopy using a HPGe detector. Auxiliary Monte-Carlo simulations were performed to determine the flux and energy distribution of the Bremsstrahlung photons. The activity thus obtained is high enough to consider the feasibility for commercial purposes of the production of M 99 o through photo-nuclear reactions. Apart from the reaction of interest, the activity of other long-lived radioactive impurities produced from M nat o ( γ, x ) reactions were determined. Highlights: Gamma induced reaction on natMo using 60, 100 and 200 MeV end point bremsstrahlung. Radiations. Study of long-lived radioactive impurities in nat-Mo(γ, x) reactions. Comparison of experimental results with the auxiliary Monte-Carlo simulation data (Geant-4 and TALYS).